Weakly cemented rock-soil mass cultural relic reinforcement grouting material as well as preparation method and application thereof
By using components such as ferroalaluminate cement and underwater dispersant in the grouting materials, the problem of poor compatibility between existing grouting materials and site soil is solved, and the durability and mechanical properties of grouting materials are improved. Meets the reinforcement needs of architectural soil ruins.
Patent Information
- Application Number
- CN202411481575.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The grouting materials for the reinforcement and grouting materials of existing building soil sites have poor compatibility with the soil of the site, which affects the appearance of the site, and their workability, mechanical properties and durability cannot meet the requirements of restoration and reinforcement.
Using a grouting material including water, silicate cement, ferroaluminate cement, composite filler, micro-expander, anti-underwater dispersant and water reducer, the partial silicate is replaced by ferroaluminate cement. Cement is used to reduce appearance differences and improve the durability and mechanical properties of the material through anti-underwater dispersants and composite fillers.
The matching of grouting materials with the original rock and soil body is improved, the durability, workingability and mechanical properties of the materials are improved, and the stability and appearance protection of the site are ensured.
Smart Images

Figure CN119306456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of repair and reinforcement of building earthen sites, and in particular to a weakly cemented rock and soil cultural relic reinforcement grouting material and a preparation method and application thereof. Background Art
[0002] Due to natural weathering erosion, disasters, and disturbances caused by human activities, a large number of earthen sites are no longer intact, and the remaining structures also have many defects, such as crack development, cement loss, and peeling. If appropriate remedial measures are not taken, the sites will gradually disappear under the action of erosion. Therefore, in order to inherit the historical and artistic value contained in them and protect these cultural heritages from further erosion, they need to be reinforced.
[0003] Grouting technology is one of the most effective methods to improve the stability of rock and soil, and has been applied in the field of site restoration and reinforcement. However, the reinforcement and restoration of site cultural relics is different from conventional grouting projects, that is, it cannot significantly change the appearance and morphology of the original soil of the site.
[0004] Therefore, there are high requirements for the key factor of grouting materials. However, there are still many problems with the grouting materials used to reinforce building earthen sites. For example, the compatibility between grouting materials and site soil is poor, which to a certain extent destroys the original appearance of the site soil, and the workability, mechanical properties and durability of grouting materials cannot meet the requirements of repair and reinforcement. In summary, in view of the technical deficiencies in the field of existing grouting materials for the reinforcement of site soil, there is an urgent need for a grouting material with good workability, good durability and good compatibility with the original soil to reinforce weakly cemented rock and soil sites. Summary of the invention
[0005] The first object of the present invention is to provide a weakly cemented rock and soil cultural relic reinforcement grouting material;
[0006] The second object of the present invention is to provide a method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material;
[0007] The third object of the present invention is to provide an application of the material obtained by the above-mentioned preparation method in the reinforcement grouting of rock and soil cultural relics.
[0008] By means of the weakly cemented rock and soil cultural relics reinforcement grouting material and the preparation method and application thereof, the matching of the grouting material with the original rock and soil is improved, and the durability, workability and mechanical properties of the above-mentioned material are improved.
[0009] Based on the above invention purpose, a weakly cemented rock and soil cultural relics reinforcement grouting material includes the following components in weight proportions: 50-150 parts of water, 31-71 parts of silicate cement, 10-30 parts of ferroaluminate cement, 19-39 parts of composite filler, 2-7 parts of micro-expansion agent, 0.5-1.5 parts of anti-underwater dispersant and 0.3-0.5 parts of water reducer.
[0010] Among them, a method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material comprises the following steps:
[0011] Dilute the anti-underwater dispersant and set it aside;
[0012] Pour water, silicate cement, ferroaluminate cement, composite filler, expansion agent, anti-underwater dispersant and water reducing agent into a mixing pot in sequence and stir;
[0013] Pour the diluted reserved anti-underwater dispersant into a stirring pot and stir evenly to obtain the weakly cemented rock and soil cultural relics reinforcement grouting material.
[0014] The present invention uses an appropriate proportion of ferroaluminate cement to replace part of the silicate cement, and can use the earthy red ferroaluminite generated after the hydration of ferroaluminate cement to reduce the appearance difference between the stone body of the grouting material and the original soil; and the ferroaluminate cement can accelerate the curing speed of the grouting material, improve the early strength and compensate for the shrinkage of ordinary silicate cement; at the same time, part of Fe2O3 is used to replace Al2O3 in the production raw materials of ferroaluminate cement, which reduces the consumption of bauxite, production costs and CO2 emissions. Therefore, by adding ferroaluminate cement, not only the minimization of the difference in appearance state and the performance enhancement effect are taken into account, but also the characteristics of energy saving and emission reduction are achieved.
[0015] Furthermore, the anti-underwater dispersant includes deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether. The weight ratio of deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether is 100-120: 40-60: 8-20: 0.8-1.0: 0.5-1.0: 2-6.
[0016] Wherein, the preparation method of the anti-underwater dispersant comprises the following steps:
[0017] Pour ethylenediamine, xanthate and deionized water into a reaction kettle and stir, and adjust the pH of the solution in the reaction kettle to 8-10;
[0018] Nitrogen is introduced into the reactor under a constant temperature environment of 15°C-20°C, and dibenzoyl peroxide and sodium lauryl sulfate are added into the reactor in sequence under the nitrogen atmosphere, and the mixture is stirred to obtain a polyethylenediamine-xanthate copolymer;
[0019] Add hydroxyethyl cellulose ether to the polyethylenediamine-xanthate copolymer in a reaction kettle, and stir to obtain an anti-underwater dispersant.
[0020] The dibenzoyl peroxide in the anti-underwater dispersant can accelerate the polymerization reaction of ethylenediamine and xanthate, and introduce a large number of amino groups; the surfactant sodium lauryl sulfate destroys the hydrogen bonds in hydroxyethyl cellulose ether, releasing a large number of free hydroxyl groups, prompting it to combine with the copolymer of ethylenediamine and xanthate to form a network structure. This network structure can form a hydrogel with water, so that the grouting material has water retention and anti-underwater dispersion effects.
[0021] When used in a dry or low humidity environment, the hydrogen atoms in the water molecules have a greater affinity with the oxygen atoms in the silica-alumina minerals, resulting in a potential water loss effect. The network structure in the anti-underwater dispersant forms a hydrogel with the water molecules, thereby preventing the water molecules from escaping. When used in a water-rich or high humidity environment, the hydrophobic groups in the polymer repel water molecules to prevent the external water from dispersing the grouting material.
[0022] The anti-underwater dispersant of the present invention has good applicability in dry or low-humidity sites and in high-humidity or water-rich environments.
[0023] Furthermore, the composite filler includes ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres, silica fume and water. The weight ratio of ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres and silica fume is 10-20: 1-5: 3-5: 2-3: 3-6.
[0024] The preparation method of the composite filler comprises the following steps:
[0025] Add ultrafine mineral powder, formation soil, diatomaceous earth and silica fume to the ball mill in sequence. Each time a raw material is added, stir slowly for 30s-40s and then stir quickly for 15s-20s to obtain a dry mixture. Among them, the formation soil and diatomaceous earth are used to improve the compatibility of the grouting material and the original soil, and the mineral powder and silica fume play the role of filling and increasing the cementitious material.
[0026] Spray water into the dry mixture three times, and wet grind for 5-10 minutes after each water addition, so that the formation soil, diatomaceous earth and silica fume can be fully attached to the surface of other powders by using surface tension, and the formation soil particles can be further ground;
[0027] Start the resistance heating device attached to the ball mill, stir slowly until the mixture is completely dry, and then stir and grind quickly for 10-20 minutes to obtain a mixture;
[0028] The mixture was transferred into a drum mixer, and hollow glass microspheres were added and mixed for 5-10 minutes to improve the workability of the slurry, thereby obtaining a composite filler.
[0029] Among them, the stratigraphic soil is taken from the area near the original site and is similar in composition to the original soil, so as to improve the compatibility of the grouting material with the site; diatomaceous earth is a sedimentary rock characterized by siliceous organisms. On the one hand, its composition further improves the compatibility of the grouting material with the weakly cemented rock and soil cultural relics, and on the other hand, its lightweight characteristics are used to reduce the self-weight of the grouting material and reduce the risk of damage to the rock and soil site caused by the grouting material's own load; hollow glass microspheres have similar weight-reducing properties to diatomaceous earth, and can also reduce the loss of fluidity of the grouting material caused by the introduction of stratigraphic soil and diatomaceous earth; ultrafine mineral powder and silica fume are used to increase the number of hydration products and improve physical and mechanical properties.
[0030] The composite filler of the invention improves the compatibility of the grouting material with the original rock and soil mass in terms of composition, and does not significantly affect the workability of the grouting material.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0032] The present invention discloses a weakly cemented rock and soil cultural relic reinforcement grouting material and a preparation method and application thereof. The present invention replaces part of ordinary silicate cement with ferroaluminate cement, thereby reducing the appearance difference between the stone body of the grouting material and the original soil; improving the early strength of the cement and compensating for the shrinkage of silicate cement; and also having the characteristics of energy saving and emission reduction.
[0033] The composite filler of the present invention can further improve the compatibility of the grouting material with the weakly cemented rock and soil cultural relics; reduce the risk that the grouting material's own load may cause damage to the rock and soil cultural relics; and improve the physical and mechanical properties.
[0034] The anti-underwater dispersant of the present invention can make the grouting material have the functions of water retention and anti-underwater dispersion, and has good applicability in dry or low-humidity ruins as well as in high-humidity or water-rich environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0036] Figure 1 It is the XRD spectrum of the grouting material stone body;
[0037] Figure 2 This is the SEM image of the grouting material stone body; DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings, but the present invention is not limited to the scope of the embodiments. The experimental methods in the following embodiments without specifying specific conditions are selected according to conventional methods and conditions, or according to the product instructions.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] Example 1
[0041] A method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material comprises the following steps:
[0042] Step 1, preparing a composite filler, a micro-expanding agent and an anti-underwater dispersant;
[0043] Step 1.1, the preparation method of the composite filler comprises the following steps:
[0044] Step 1.11, ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres and silica fume are weighed in a weight ratio of 10-20:1-5:3-5:2-3:3-6, and the ultrafine mineral powder, formation soil, diatomaceous earth and silica fume are added to the ball mill in sequence, and each time a raw material is added, it is first slowly stirred for 30s-40s and then quickly stirred for 15s-20s to obtain a dry mixture; wherein the formation soil and diatomaceous earth are used to improve the compatibility of the grouting material with the original soil, and the mineral powder and silica fume play the role of filling and increasing the cementitious material;
[0045] Step 1.12, spraying water into the dry mixture three times, wet grinding for 5-10 minutes after each water addition, using surface tension to make the formation soil, diatomaceous earth and silica fume fully adhere to the surface of other powders, and further grinding the formation soil particles; wherein the weight ratio of water to the above components is 1:10, and the above components are solid raw materials composed of ultrafine mineral powder, formation soil, diatomaceous earth and silica fume;
[0046] Step 1.13, start the resistance heating device attached to the ball mill, slowly stir until the mixture is completely dry, and then quickly stir and grind for 10 minutes to 20 minutes to obtain a mixture;
[0047] Step 1.14, transfer the mixture into a drum mixer, add hollow glass microspheres and mix for 5 minutes to 10 minutes to improve the workability of the slurry, and obtain a composite filler.
[0048] Step 1.2, the preparation method of the anti-underwater dispersant comprises the following steps:
[0049] Step 1.21, weigh deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether in a weight ratio of 100-120:40-60:8-20:0.8-1.0:0.5-1.0:2-6;
[0050] Step 1.22, pour ethylenediamine, xanthate and deionized water into a reaction kettle in a weight ratio and stir for 30s-60s, and adjust the pH of the solution in the reaction kettle to 8-10;
[0051] Step 1.23, introducing nitrogen gas under a constant temperature environment of 15° C. to 20° C., adding dibenzoyl peroxide and sodium lauryl sulfate into the reaction kettle in sequence under the nitrogen atmosphere, and stirring to obtain a polyethylenediamine-xanthate copolymer;
[0052] Step 1.24, adding hydroxyethyl cellulose ether to the polyethylenediamine-xanthate copolymer in the reaction kettle, stirring to obtain an anti-underwater dispersant.
[0053] Step 1.3, the preparation method of the micro-expanding agent comprises the following steps:
[0054] Step 1.31, pumice powder, coral stone, flue gas desulfurization gypsum, and ultrafine calcium sulfoaluminate are weighed in a weight ratio of 42-48:14-26:32-38:0.12-0.35;
[0055] Step 1.32, crushing the pumice powder, coral stone and flue gas desulfurization gypsum with a crusher, adding them to a ball mill and grinding them for 20 minutes to 30 minutes to obtain a first mixture;
[0056] Step 1.33, adding ultrafine calcium sulfoaluminate to the first mixture in step 1.32, and dispersing it by a resonance mixer for 10 min-20 min to obtain a second mixture, wherein the ultrafine calcium sulfoaluminate is introduced to promote the formation of calcium sulfoaluminate by utilizing its crystal nucleation effect during the calcination process in step 1.34;
[0057] Step 1.34, calcining the second mixture obtained in step 1.33 to 980° C.-1170° C. and keeping the temperature for 45 min-90 min to obtain a calcined product;
[0058] Step 1.35, grinding the calcined product for 10 min-30 min to obtain a micro-expanding agent.
[0059] Step 2, diluting the anti-underwater dispersant for standby use;
[0060] Step 3, weigh the following components in parts by weight: 50-150 parts of water, 31-71 parts of silicate cement, 10-30 parts of ferroaluminate cement, 19-39 parts of composite filler, 2-7 parts of micro-expansion agent, 0.5-1.5 parts of anti-underwater dispersant and 0.3-0.5 parts of water reducer.
[0061] Step 31, pouring water, silicate cement, ferroaluminate cement, composite filler, expansion agent, anti-underwater dispersant, and water reducing agent into a stirring pot in sequence for stirring;
[0062] Step 32, pour the diluted standby anti-underwater dispersant into a stirring pot and stir evenly to obtain a weakly cemented rock and soil cultural relic reinforcement grouting material.
[0063] Among them, the water reducing agent is a naphthalene-based high-efficiency water reducing agent.
[0064] Example 2
[0065] Based on the above embodiments,
[0066] The ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres and silica fume of the composite filler in step 1.1 are weighed in a weight ratio of 10:1:3:2:3; the weight ratio of the solid raw materials composed of water and ultrafine mineral powder, formation soil, diatomaceous earth and silica fume is 1:10;
[0067] In step 1.2, the weight ratio of deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate and hydroxyethyl cellulose ether in the underwater anti-dispersant is 100:40:8:0.8:0.5:2;
[0068] Step 1.3: weigh the pumice powder, coral stone, flue gas desulfurization gypsum, and ultrafine calcium sulfoaluminate in the micro-expansion agent in a weight ratio of 42:14:32:0.12;
[0069] In step 3, the following components are weighed in parts by weight: 50 parts of water, 71 parts of silicate cement, 10 parts of ferroaluminate cement, 19 parts of composite filler, 2 parts of micro-expansion agent, 0.5 parts of anti-underwater dispersant, and 0.3 parts of naphthalene-based high-efficiency water reducer.
[0070] Example 3
[0071] Based on the above embodiments,
[0072] In step 1.1, the weight ratio of the composite filler, ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres, and silica fume is 12:2:4:3:4; the weight ratio of the solid raw materials composed of water and ultrafine mineral powder, formation soil, diatomaceous earth, and silica fume is 1:10;
[0073] Deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether in the anti-underwater dispersant in step 1.2 are weighed in a weight ratio of 105:44:10:0.8:0.6:3;
[0074] Step 1.3: weigh pumice powder, coral stone, flue gas desulfurization gypsum, and ultrafine calcium sulfoaluminate in the micro-expansion agent in a weight ratio of 43:16:35:0.16;
[0075] In step 3, the following components are weighed in parts by weight: 150 parts, 31 parts of silicate cement, 30 parts of ferroaluminate cement, 39 parts of composite filler, 7 parts of micro-expansion agent, 1.5 parts of anti-underwater dispersant, and 0.5 parts of naphthalene-based high-efficiency water reducer.
[0076] Example 4
[0077] On the basis of Example 1, in step 1.2 of this example, the anti-underwater dispersant is at least one of hydroxyethyl methylcellulose or hydroxypropyl methylcellulose.
[0078] Example 5
[0079] Based on Example 1, this example does not include an anti-underwater dispersant; the following components in weight proportions are weighed: 50-150 parts of water, 31-71 parts of Portland cement, 10-30 parts of ferroaluminate cement, 19-39 parts of composite filler, 2-7 parts of micro-expansion agent and 0.3-0.5 parts of water reducer.
[0080] Example 6
[0081] On the basis of Example 1, deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether in the anti-underwater dispersant in step 1.2 are weighed in a weight ratio of 80:69:35:0.2:10:20. The weight ratios of the components of the anti-underwater dispersant in this example are outside the weight ratios of the components of the anti-underwater dispersant of the present invention.
[0082] Example 7
[0083] On the basis of Example 1, the composite filler of this example includes the following components in parts by weight: 4 parts of talc, 5 parts of perlite, and 4 parts of formation soil. The preparation method of the composite filler is the same as the preparation method of the composite filler in Example 1.
[0084] Example 8
[0085] On the basis of Example 1, in step 1.11, the ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres and silica fume in the composite filler are weighed in a weight ratio of 5:8:6:1:10. The weight ratios of the components of the composite filler of this example are outside the weight ratios of the components of the composite filler of the present invention.
[0086] Example 9
[0087] The construction properties and mechanical properties of the grouting materials prepared in Examples 2-8 were tested. The test results are shown in Table 1.
[0088] Among them, the fluidity test: (1) Place the glass plate in a horizontal position, wipe the glass plate and the cone section mold with a wet cloth to make the surface wet but without water stains. Place the cone section mold in the center of the glass plate and cover it with a wet cloth for use; (2) Quickly inject the mixed slurry into the cone section mold and scrape it flat with a scraper; (3) Lift the cone section mold in the vertical direction and start the stopwatch at the same time. Let the slurry flow on the glass plate for 30 seconds, use a ruler to measure the maximum diameter of the flowing part in two directions perpendicular to each other, and take the average value as the fluidity of the slurry; (4) Repeat the above steps and measure again.
[0089] Water separation rate test: Take 1000mL of evenly stirred grouting material, inject the grouting material into a graduated glass measuring cylinder, then cover it with a glass plate, let it stand for 2 hours, read the volume of the supernatant, calculate its percentage to the total volume, and then get the water separation rate.
[0090] Compressive strength test: Use a 40×40×40mm mold to form the specimen, demould it after curing for 1d under standard curing conditions, and then standard cure it to 3d and 7d age. Use a pressure testing machine to uniformly load it at a rate of 50N / s±10N / s until it is destroyed. The test result is the average value of 6 specimens.
[0091] Softening coefficient test: the ratio of the compressive strength of the grouting material in the water-saturated state to the compressive strength in the dry state. Initial setting time and final setting time test: prepare the grouting material test mold, from the time of adding water to the time of setting, the time when the test needle of the measuring instrument sinks into the clean slurry 4mm±1mm from the bottom plate is the initial setting time, and then continue to observe, and the time when the final setting test needle sinks into the clean slurry no more than 0.5mm is the final setting time.
[0092] Expansion rate test: Use a comparator to measure the initial specimen length and the specimen length at 28 days of age. Expansion rate = (28 days of age specimen length – initial specimen length) / initial specimen length.
[0093] Table 1
[0094]
[0095] It can be seen from Table 1 that the grouting materials prepared in Example 2 and Example 3 are within the protection scope of the present invention. The softening coefficient of the grouting materials prepared in Example 2 and Example 3 is greater than 0.85, and they have good water resistance and can be used in important buildings or structures that are in water or humid environments for a long time. The anti-underwater dispersant used in Example 4 is at least one of hydroxyethyl methylcellulose or hydroxypropyl methylcellulose. The components and preparation method of the anti-underwater dispersant in Example 4 are different from the components and preparation method of the anti-underwater dispersant of the present invention. Example 5 does not include the anti-underwater dispersant on the basis of Example 2. The softening coefficients of Examples 4 and 5 are less than 0.70. Therefore, the grouting materials of Examples 4 and 5 have poor water resistance and may not be able to guarantee the strength and stability of buildings or structures when used in a humid or watery environment.
[0096] The grouting materials prepared in Examples 2 and 3 have good compressive strength. At the same time, the solidification time of the grouting materials prepared in Examples 2 and 3 is long, which can meet the requirements of repair and reinforcement. The strength performance of Example 4 can meet the requirements, but its solidification time is too short, which is not convenient for construction operations in actual projects; Example 5 has good fluidity, but its excessive water separation rate will seriously affect the effect after reinforcement; Examples 6, 7, and 8 have low fluidity, which will significantly affect the workability during the construction process, and their water separation rates are all greater than 5%, which are unstable slurries.
[0097] Example 10
[0098] Under different grouting pressures, the grouting material can be effectively injected into the loose soil, indicating that the grouting material of the present invention has good workability; on the other hand, there is no significant difference in appearance between the soil after grouting and the original soil, which complies with the principle of not significantly changing the appearance of the original site soil in cultural relics protection. The grouting material of the present invention has good matching or compatibility with the original soil.
[0099] The XRD spectrum of the grouting material stone body prepared in Example 2 is as follows Figure 1 As shown, the SEM image of the grouting material stone body prepared in Example 2 is as follows Figure 2 As shown by Figure 1 and Figure 2 It can be seen that after the grouting material solidifies, the CSH gel in it plays a major cementing role, thereby reinforcing the loose soil to a relatively stable state; Aft is an expansive crystal that can fill the gel pores of the grouting material, playing a reinforcing and anti-erosion role.
[0100] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A weakly cemented rock and soil cultural relics reinforcement grouting material, characterized in that: The invention comprises the following components in parts by weight: 50-150 parts of water, 31-71 parts of silicate cement, 10-30 parts of ferroaluminate cement, 19-39 parts of composite filler, 2-7 parts of micro-expansion agent, 0.5-1.5 parts of anti-underwater dispersant and 0.3-0.5 parts of water reducing agent.
2. The weakly cemented rock and soil cultural relics reinforcement grouting material according to claim 1 is characterized in that: The anti-underwater dispersion agent includes deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate, and hydroxyethyl cellulose ether.
3. The weakly cemented rock and soil cultural relics reinforcement grouting material according to claim 2 is characterized in that: The weight ratio of deionized water, ethylenediamine, xanthate, dibenzoyl peroxide, sodium lauryl sulfate and hydroxyethyl cellulose ether is 100-120:40-60:8-20:0.8-1.0:0.5-1.0:2-6.
4. The weakly cemented rock and soil cultural relics reinforcement grouting material according to claim 1, characterized in that: The composite filler includes ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres, silica fume and water.
5. The weakly cemented rock and soil cultural relics reinforcement grouting material according to claim 4, characterized in that: The weight ratio of ultrafine mineral powder, formation soil, diatomaceous earth, hollow glass microspheres and silica fume is 10-20:1-5:3-5:2-3:3-6.
6. A method for preparing a grouting material for reinforcing weakly cemented rock and soil cultural relics, characterized in that: The weakly cemented rock and soil cultural relics reinforcement grouting material comprises any one of claims 1 to 5, and the preparation method comprises the following steps: Dilute the anti-underwater dispersant and set it aside; Pour water, silicate cement, ferroaluminate cement, composite filler, expansion agent, anti-underwater dispersant and water reducing agent into a mixing pot in sequence and stir; Pour the diluted reserved anti-underwater dispersant into a stirring pot and stir evenly to obtain the weakly cemented rock and soil cultural relics reinforcement grouting material.
7. The method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material according to claim 6, characterized in that: The preparation method of the anti-underwater dispersant comprises the following steps: Pour ethylenediamine, xanthate and deionized water into a reaction kettle and stir, and adjust the solution in the reaction kettle to alkaline; Under a nitrogen atmosphere, dibenzoyl peroxide and sodium lauryl sulfate were sequentially added into a reaction kettle, and stirred to obtain a polyethylenediamine-xanthate copolymer; Add hydroxyethyl cellulose ether to the polyethylenediamine-xanthate copolymer in a reaction kettle, and stir to obtain an anti-underwater dispersant.
8. The method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material according to claim 7, characterized in that: The pH of the solution in the reaction kettle was adjusted to 8-10.
9. The method for preparing a weakly cemented rock and soil cultural relic reinforcement grouting material according to claim 7, characterized in that: Nitrogen was introduced into the reactor under a constant temperature of 15°C-20°C, and dibenzoyl peroxide and sodium lauryl sulfate were added into the reactor in sequence under the nitrogen atmosphere.
10. Use of the material prepared by the preparation method according to any one of claims 6 to 9 in the reinforcement grouting of rock and soil cultural relics.
Citation Information
Patent Citations
High-performance superfine cement based grouting material for microfissuring and silty fine sand soil grouting treatment and application of grouting material
CN107619236A
Hydrophobic grouting material for sandy gravel stratum and preparation method of hydrophobic grouting material
CN116283165A
Cement-based grout composition
JP2000034156A
Injection composition for grout
KR101793650B1
Underwater Non-Dispersible Quick-Setting and Rapid-Hardening Cement-Based Composite Material and Preparation Method and Application Thereof
US20180290923A1
Cited By
Strong-diffusivity micro-fracture rock mass interface reinforcing grouting material and preparation method thereof
CN119613057A
A highly diffusible micro-crack rock interface enhanced grouting material and preparation method thereof
CN119613057B
Anti-weathering coating for red sandstone cultural relics and preparation method thereof
CN119639342A